Vegetarianism and Ahiṃsā in the Anuśāsanaparvan of the Mahābhārata - Scarabel, Anna (Interdisziplinäre Zeitschrift für Südasienforschung, 2020)
The adhyāyas 114 to 117 of the Anuśāsanaparvan (the 13th book of the Mahābhārata) introduce the topic of ahiṃsā (non-violence) and its relation to vegetarianism. All in all, the text enjoins that following a vegetarian diet is the greatest non-violent practice. However, several verses of this section allow practices related to Vedic sacrifice, which include meat offerings. In view of the principles of non-violence, such an “exception” to the ahiṃsā rule may be seen by some as a logical inconsistency. Instead, I argue that such apparent contradiction can be resolved if we consider that the Mahābhārata addresses different audiences. On one side, there are those leading a contemplative life (nivṛtti), aiming at spiritual upliftment, who follow the path of ahiṃsā and maintain a vegetarian diet. On the other side, those engaged in an active life (pravṛtti) perform Vedic rituals in view of worldly objects and relish the animals sacrificed to the gods. As a result of their class duty, Hindu warriors may also hunt and eat animals. In this article, I further implement my arguments and investigate the relation between non-violence and vegetarianism in the Mahābhārata.